A randomized controlled trial of varenicline and brief behavioral counseling delivered by lay counselors for adolescent vaping cessation: Study protocol - Schuster, Randi M.; Cather, Corinne; Pachas, Gladys N.; Nielsen, Lindsay; Iroegbulem, Vanessa; Dufour, Jason; Potter, Kevin; Levy, Sharon; Gray, Kevin M.; Evins, A. Eden (Frontiers in Psychiatry, 2023)
Background: Approximately one-fifth of high-school seniors and college students currently vape nicotine. Adolescents express a desire to quit vaping, and case reports have shown promise for e-cigarette tapering with dual behavioral and pharmacologic therapies. However, there are no published clinical trials to date that test these intervention approaches for adolescent nicotine vaping cessation. In this three-arm randomized, placebo-controlled, parallel-group study, we aim to assess the efficacy of varenicline in combination with brief behavioral counseling and texting support on vaping cessation in adolescents dependent on vaped nicotine. Methods: The study will enroll 300 individuals between the ages of 16-25 with daily or near-daily nicotine vaping who reside in the Greater Boston area. Participants will be randomly assigned in a 1:1:1 ratio in blocks of six to one of the three arms: 1) a 12-week course of varenicline titrated to 1mg bid, brief behavioral counseling delivered by a lay counselor, and an introduction to This is Quitting (TIQ) texting support created by the Truth Initiative; 2) a 12-week course of placebo, brief behavioral counseling, and TIQ; and 3) 12 weeks of enhanced usual care, consisting of advice to quit and an introduction to TIQ. The primary outcome will be biochemically verified continuous vaping abstinence at the end of the treatment (week 12). Secondary outcomes include continuous abstinence at follow-up (week 24), 7-day point prevalence abstinence at weeks 12 and 24, safety and tolerability of varenicline in an adolescent vaping population, as well as change in mood and nicotine withdrawal symptoms across the intervention period. Exploratory outcomes include change in comorbid substance use behaviors and nicotine dependence. Analysis will be intent-to-treat, with multiple imputation sensitivity analyses for participants with missing or incomplete outcome data. Discussion: This is the first study to evaluate varenicline in combination with a novel, brief, lay counselor delivered vaping cessation program for adolescents who vape nicotine. Results will inform clinicians on the effectiveness and acceptability of this promising, but not yet tested intervention.